Peran Ekowisata Terhadap Peningkatan Kesejahteraan Masyarakat Dusun Batu Katak - Ikhlas Ramadhan (Tourism, Hospitality And Culture Insights Journal, 2023)
Ecotourism is environment-based tourism that prioritizes the principles of sustainability and provides benefits to local communities. One of the benefits that can be provided by ecotourism is to increase employment opportunities for local communities. The purpose of this study was to analyze the level of community welfare with the Batu Katak ecotourism, Langkat district. The method used in this research is qualitative method. The data used are primary data taken directly by conducting interviews with local communities and secondary data obtained from government agencies, namely the Batu Katak village office in the form of the population in Batu Katak village and the Batu Katak website. The results of the study show that the existence of Batu Katak Ecotourism plays an important role in the survival of the community because the community can feel the impact directly or indirectly such as being able to increase income, knowledge and experience more from ecotourism activities. Based on the research, it can be concluded that ecotourism activities carried out in Batu Katak play a role in increasing people's income directly or indirectly and this ecotourism activity has a positive impact on the welfare of the Batu Katak village community and it is hoped that Batu Katak Ecotourism in the future can increase community welfare as a whole.